Problematika Siswa Dan Solusinya Dalam Perspektif Manajemen Pendidikan: Kajian Strategi Pengelolaan Kesiswaan Di Era Digital - Haidar Umar Zaky; Moh. Syukron; Moh. Riansyah Umasugi (El-Mudarris: Jurnal Manajemen Pendidikan dan Kepemimpinan Sekolah, 2026)
Digital transformation has fundamentally changed educational systems while giving rise to various student-related challenges, including declining learning motivation, excessive dependence on digital devices, disciplinary issues, cyberbullying, and reduced engagement in the learning process. This study aims to analyze student problems in the digital era and examine student management strategies as a solution from the perspective of educational management. The study employed a qualitative approach using a library research method through a literature review. Secondary data were collected from SINTA-accredited national journals, Scopus-indexed international journals, books, conference proceedings, and other scholarly publications published between 2020 and 2025. The literature was retrieved from Google Scholar, Scopus, Dimensions, Garuda, and SINTA databases and analyzed using content analysis and thematic analysis. The findings indicate that student problems are influenced by interconnected internal and external factors, requiring comprehensive management strategies. Effective approaches include guidance and counseling services, character education, strengthening digital literacy, and collaboration among schools, families, and communities. These findings highlight the strategic role of student management in creating an adaptive, preventive, and sustainable educational environment that supports students' academic achievement, character development, and well-being in the digital era.